Sheffield Hallam University - Centre for Sport and Exercise Science (CSES) (2008)
The Centre for Sport and Exercise Science (CSES) boasts one of the largest physical activity and sport-related portfolios of research expertise in the UK, if not Europe. It has a wide range of clients from the public and private sector, and operates across three main disciplines